Análise de produto com enfoque modular com relação à manufatura e montagem - Machado, Jairo (2013)
This paper presents the study of the design methodology of modular products called MFD (Modular Function Deployment ), and its application in developing new products with a focus on manufacturing and assembly. Initially it is an introduction to methods of modular product design in order to identify its characteristics and peculiarities. So is an analysis and evaluation of the method and its MFD design tools from the point of view of manufacturing and assembly, in order to verify which modularization guidelines can help in evaluating the product / module with respect to manufacturability and assembly. These guidelines are considered aspects of disassembly, maintenance, upgradability, reusability, among others, to ensure that the manufacturing and assembly, are considered from the beginning of the design in decisions relating to modularisation. The analysis of the guidelines will allow modularization reflect on the process of manufacturing and assembly process, providing sufficient information to develop design concepts of modular products aimed at manufacturing and assembly. In this paper an analysis is made with reference to the use of the dendrogram for use in planning the modularization of the product with respect to the planning of manufacturing and assembly. We will present a case study of a product, applying the methodology MFD in a hewer of wood